Raia das virtudes: elementos para construir uma narrativa de Madame Satã - Dorsa Neto, Raphael (2024)
The research aims to gather information for the story line to script making for Virtues Beach – A Story about Madame Satã, a feature-length documentary about the trickster, artist, outcast, father, and man João Francisco dos Santos, the myth Madame Satã (1900-1976). Conducted through bibliographic and documentary analyses of historic, social and political phenomena, the research seeks to build, from the mosaic of memories, an understanding the complexity of the narrated character and the collective imagination persistence about him, even almost fifty years after his death. Additionally, the research brings highlights excerpts from interviews conducted by the researcher with people who lived or had contact with Madame Satã in the last decade of his life. The research addresses the constitutive panorama of the myth as a continuous interaction between mythical narrative and symbolic representations present in culture, hegemonic and counter-hegemonic discourses throughout the recent history of Brazil. It is a specific approach that involves various themes related to João Francisco's life, such as slavery, racism, homophobia, marginality, spirituality, dictatorship, and art. The research fulfillment reveals the depth and trouble of classifying the countless facets and different tribes of Madame Satã, offering different perspectives/voices about him using underlying epistemological assumptions, considering that concepts, definitions, images, as well as power structures, never apply in isolation but semantically intersect in networks. These assumptions serve as a reference point to relate their interactions with the assembling of texts, by bringing together heterogeneous elements to compose a narrative with political and subversive potential, questioning established power structures. The work’s main title, Praia das Virtudes, refers to the time/place where João could still experience small moments of innocence and ingenuity, where he could be a child, even though he briefly passed through childhood.